3d‐Transition metal doped two-dimensional SnTe: Modulation of thermoelectric properties. (June 2022) - Biswas, Raju K.; Banerjee, Paramita; Pati, Swapan K.
Abstract: Newly explored hexagonal phase of two-dimensional (2D) SnTe has been shown to be thermodynamically as well as dynamically stable and it exhibits high thermoelectric performance. In this study, we mainly investigate the effect in terms of electrical and thermal transport properties due to 3d-transition metal (TM) doping in 2D-SnTe. Based on first-principles calculations and Boltzmann transport theory, our study encompasses that both V and Mn doped SnTe exhibit moderate intrinsic carrier mobility because of lower elastic constant and higher carrier effective mass. Furthermore, the incorporation of V and Mn in the atomic layer of SnTe slightly enhances the Seebeck coefficient than pristine. While calculating thermal transport coefficient, V and Mn doping show a significant reduction in lattice thermal conductivity than pristine 2D SnTe due to enhanced phonon-phonon scattering strength, and as a result, we achieve very high zT ~ 2.24 at 900 K for Mn-doped SnTe. The replacement of Sn by cost-effective and environmentally-friendly 3d-TM with enhanced thermoelectric performance by 5%, would be beneficial during the energy crisis. Graphical Abstract: ga1 Highlights: Hexagonal phase of two-dimensional (2D) SnTe has been computationally studied. Role of 3d-transition metal in 2D-SnTe is examined for thermoelectric applications. Boltzmann transport theory along with DPT is used to compute transport parameters. Substitution of Sn by cost-effective and abundant 3d-TM would be beneficial.